Management and Control of Trichomonas vaginalis Infection: A Recent Study - Padmalaya Das (Highlights on Medicine and Medical Research Vol. 10, 2021)
Trichomonas vaginalis is the etiologic agent of trichomoniasis, the most common non-viral sexually transmitted disease (STD) in the world. The infection occurs in the female and male urogenital tract and humans are the only natural host for the parasite. In this chapter, the Management of Trichomonas vaginalis Infection as well as prevention are well described. Multidose metronidazole has been found to be superior to single-dose metronidazole for the treatment of trichomoniasis. The drug is well tolerated with minimal adverse reactions. The authors suggested that treating trichomoniasis in women with a 7-day dose of metronidazole should be the first line of treatment.